Application of Communication in Madratsah - Wajnah Wajnah; Abidah Abidah (Budapest International Research and Critics University, 2021)
Education as a system is an organization that aims to create graduates who have multi-intelligence so can manifest themselves as part of civil society.To achieve the goals of education above, Communication within organizations is an important element of that form and allows an organization to work. The fact in the field of attention of madrasa to communication is very low. This research will discuss the Model and Application of Islamic Educational Organization Communication (A Research on MAN I Takengon, Central Aceh, Aceh). This study aims to descriptives of the model and application of organizational communication. This study used a qualitative approach, data collected through observation, in-depth interviews, and documents about various communication models used, then analyzed data, by describing qualitatively using the concept of miles and huberman. The research results shows that the communication model used varies, no ones model of communication is superior. Communication tools both internal and external relatively the same, the use of information powerless computing or ICT has not been maximized. It is not significant obstacles were found in establishing internal and external communications, although the committee and parents were not proactive in establishing communication with the madrasa.